MUATAN PENDAMPINGAN PASTORAL DALAM BUDAYA MAPALUS:BERANTANG DAN SUMAKEY BAGI KELUARGA BERDUKA DI MINAHASA, KAWANGKOAN - Yohan Brek; Christina C Taroreh (POIMEN Jurnal Pastoral Konseling, 2023)
Culture becomes a distinctive color in society. People appreciate every culture that is present as a form of sustaining existing social life. The culture that has existed because of the spirit of the ancestors continues to revive social values that aim to strengthen. Pastoral assistance is present and becomes a content in the mapalus culture: berantang and sumakey as a form of love and concern for others. This existential pastoral care gives color that culture can reveal the purpose and function of pastoral care to show that humans are creatures who live together. In the end, this research, which is based on various literature reviews but also obtained from observations and data sources, is expected to be a contribution but also a supportive spirit so that the culture of berantang and sumakey is maintained and preserved without ignoring the values contained.